2012
DOI: 10.1016/j.taap.2012.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Development of monoclonal antibodies to human microsomal epoxide hydrolase and analysis of “preneoplastic antigen”-like molecules

Abstract: Microsomal epoxide hydrolase (mEH) is a drug metabolizing enzyme which resides on the endoplasmic reticulum (ER) membrane and catalyzes the hydration of reactive epoxide intermediates that are formed by cytochrome P450s. mEH is also thought to have a role in bile acid transport on the plasma membrane of hepatocytes. It is speculated that efficient execution of such multiple functions is secured by its orientation and association with cytochrome P450 enzymes on the ER membrane and formation of a multiple transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The product of EPHX1 gene, mEH, is a drug metabolizing enzyme found on the endoplasmic reticulum of many tissues and is responsible for catalyzing the hydration of reactive epoxide intermediates that are formed bycytochrome P450s, including PAHs [10,13]. The results shown mEH protein was high expression in persistence non-remission patients compared to control group.…”
Section: Discussionmentioning
confidence: 93%
“…The product of EPHX1 gene, mEH, is a drug metabolizing enzyme found on the endoplasmic reticulum of many tissues and is responsible for catalyzing the hydration of reactive epoxide intermediates that are formed bycytochrome P450s, including PAHs [10,13]. The results shown mEH protein was high expression in persistence non-remission patients compared to control group.…”
Section: Discussionmentioning
confidence: 93%
“…Table 1 shows the monoclonal antibodies to human mEH developed in the previous study and grouped into five groups depending on their epitope selectivities (Duan et al , 2012). Using five antibodies, one from each type (type I: 5D8; type II: K4F8; type III: K2B7; type IV: 6E3; type V: 2G2), we examined the expression of mEH epitopes in various human cells by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…In the previous study, we have shown that the HCC line Huh-1 and the glioblastoma cell line LN-71 release mEH into the culture medium whereas other cell lines did not (Duan et al , 2012). It reminded us preneoplastic antigen (PNA) which had been described as an antigen in preneoplastic foci in livers that is released into the blood (Okita and Farber, 1975), and later found to be immunologically identical to mEH (Levin et al , 1978).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations